Preservation Kedidi Dance through Art Education: Social Roles and Strategies for Cultural Sustainability - M. Adha Al Kodri; Asyraf Suryadin; Rita Zahara (Journal of General Education and Humanities, 2026)
Kedidi Dance, a cultural heritage of the West Bangka community in the Bangka Belitung Islands, is increasingly challenged by modernization, shifting social functions, and declining youth engagement. This study investigates the role of art education in preserving Kedidi Dance, examines its evolving social functions, and identifies strategies to sustain its continuity amid socio-cultural change. Using a descriptive qualitative design, data were collected through observation, in-depth interviews, and documentation involving the leader and members of the Mawar Putih martial arts school, dancers, and community members in Benteng Kota Village, Tempilang District. The data were analyzed through data reduction, display, and conclusion drawing. The findings reveal that art education functions as a key mechanism for transmitting cultural values, strengthening local identity, and supporting intergenerational continuity. Kedidi Dance has shifted from communal folk entertainment toward a medium of cultural education and public performance while retaining its core values. The novelty of this study lies in positioning art education as an adaptive preservation mechanism that connects cultural transmission, social transformation, and community participation. This study contributes an integrative preservation framework based on institutional strengthening, community involvement, artistic openness, and local government collaboration.